2006
DOI: 10.1186/1472-6963-6-56
|View full text |Cite
|
Sign up to set email alerts
|

The feminization of the medical work force, implications for Scottish primary care: a survey of Scottish general practitioners

Abstract: Background: The number of women working in general practice internationally has been steadily rising. In Scotland there have been concerns that such a change may lead to increased part-time working and subsequently to a fall in available general practice manpower despite an apparently rising overall number of general practitioners. However, there is very little information on the actual hours worked by men and women general practitioners or on the types of work they are undertaking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
41
0
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 10 publications
4
41
0
4
Order By: Relevance
“…This, however, appears to be a relatively minor problem, as the same gender shift could result in a 20-25 percent reduction in recruitment to core specialties such as surgery and anesthesiology, which may have even more serious consequences. Such a perspective has been described by others also [28][29][30] and appears to remain a global medical challenge in that doctors will continue to favor part-time employment if they do not obtain sufficient flexibility in their full-time working conditions. In addition to individual labor supply and working hours, the number of hospital physicians needed in the future will depend on several factors.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This, however, appears to be a relatively minor problem, as the same gender shift could result in a 20-25 percent reduction in recruitment to core specialties such as surgery and anesthesiology, which may have even more serious consequences. Such a perspective has been described by others also [28][29][30] and appears to remain a global medical challenge in that doctors will continue to favor part-time employment if they do not obtain sufficient flexibility in their full-time working conditions. In addition to individual labor supply and working hours, the number of hospital physicians needed in the future will depend on several factors.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to individual labor supply and working hours, the number of hospital physicians needed in the future will depend on several factors. First, the lower working hours observed for women is not restricted to hospital care [29]. Therefore, long-term policies should consider hospital and general practice recruitment, as well as considering any central versus rural dimensions, if we are to address these challenges in the next 15-20 years.…”
Section: Discussionmentioning
confidence: 97%
“…Although researchers in other countries have traditionally used weekly work hours and/or full-time/part-time status (or full-time equivalents) to measure work effort [5,7,17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34], data on these variables were not available for our study. To provide information on the physician workforce in Japan that is more detailed, it would be important for future research to consider these variables.…”
Section: Limitations Of the Study And Suggestions For Future Researchmentioning
confidence: 99%
“…To provide information on the physician workforce in Japan that is more detailed, it would be important for future research to consider these variables. However, it is likely that the difference in work effort between male and female physicians will become even larger if their work hours and/or full-time/part-time status are taken into account; studies worldwide have so far demonstrated that, as a group, practicing female physicians work fewer hours [5,7,[21][22][23][24][25][26][27][28][29][31][32][33][34] and are more likely to be employed part-time [17,25,29,30,33] than their male colleagues.…”
Section: Limitations Of the Study And Suggestions For Future Researchmentioning
confidence: 99%
“…Globally, women doctors work fewer hours in all age groups than their male counterparts, and take time off for child rearing. McKinstry et al 4 fret that 'the rapidly increasing proportion of women in general practice [in Scotland] may lead to an increasing shortfall of medical availability in the future if current work patterns are maintained' . The feminist response might be that such work patterns should not be maintained, but should rather be adapted to be in harmony with the changing professional demographics, taking into account inter alia that women generally stay in the workforce longer and retire later in life.…”
mentioning
confidence: 99%